Challenges, coping and future plans of aging parents who have older children with special needs - Ilustre, Ana Maria Cruz (Animo Repository, 2021)
This study aims to look into the challenges, coping and future plans of aging parents who have adult children with special needs. This employed a qualitative research design and data was analyzed using thematic analysis. The researcher interviewed 10 parents aged 60 and above who have at least one child with special needs. Interviews were done online due to the COVID-19 Pandemic. This was to ensure the safety of both parties. Based on the results, 6 common themes emerged for challenges. The researcher also found 6 different coping strategies commonly used by the participants. This was later categorized into either problem focused or emotion focused coping. Aside from this, 3 common themes also surfaced for future plans. For Challenges the common themes that were discussed were Emotional Challenges, Inadequate Services and Opportunities, Stigmatization, Pandemic Related Issues, Financial Challenges and Physical Challenges. For Coping, the strategies that were commonly used were Acceptance of the Condition, Emotional and Instrumental Social Support, Adaptive Distractions Spirituality, Open Communication and Involvement in advocacies and Organizations. Finally, for future planning, parents mentioned that passing of responsibility, securing finances and promoting independence were among their initial ideas. In conclusion, aging parents with adult children with special needs experience more challenges in their day to day lives as compared to their younger counterparts. Among these challenges are preparing for their children’s future. Although, a lot of these parents are able to cope and get by, majority of them still expressed the need for further support and acceptance especially from society.